Non-food agro-industrial technology: potential of Catharanthus roseus based on the biosynthesis of the secondary metabolites vinblastin and vincristin (Agroindustria, Sociedad y Ambiente, 2022)
Catharanthus roseus is an apocynacea widely distributed in the Ecuadorian Amazon, which possesses the secondary metabolites vinblastine and vincristine, which gives it a high potential in the treatment of different diseases, including cancer, but with the disadvantage that the concentration of these metabolites in the plant is very low, so its use for pharmacological purposes is required. In order to determine the importance of the mechanisms to achieve the biosynthesis of the secondary metabolites vinblastine and vincristine for its subsequent use for the control of diseases in humans, particularly those oncological diseases where the cost of drugs, prevents access to treatment to most of the population, a systematic review was conducted in the databases SCOPUS, GOOGLE ACADEMIC REDALYC, SCIELO and LATINDEX. The research carried out shows that the Catharanthus roseus species can be used for the control of various diseases, including several types of cancer; however, given that its concentration is very low in plants, its biosynthesis is required, which according to the results found is achieved through in vitro propagation.
Keywords: Amazonia, biosynthesis, cancer, cancer, pharmacology, nanoparticles.